Optimalisasi Manajemen Usaha dan Pemasaran Digital KWT dan BUMDesa untuk Kemandirian Ekonomi Desa Kesiut: Pengabdian - Putra, M Doni Permana; Ardana, Putu Doddy Heka; Gunadi, I Gusti Ngurah Bagus (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Kesiut Village in Kerambitan District, Tabanan Regency, Bali, has strong agricultural potential, supported by the Merta Sari Werdhi Women's Farmers Group (KWT) and the Amerta Dana Village-Owned Enterprise (BUMDesa). The KWT operates in the production and trade of agricultural products and catfish farming, while the BUMDesa has expanded its business into the agricultural industry. However, both institutions face significant challenges in business management, production processes, marketing, and financial reporting. This community service program is implemented using a Participatory Action Research (PAR) approach through intensive training (business management, production, finance, online marketing), procurement of production equipment and waste bins, creation of signage and social media for the business, and ongoing mentoring. The implemented solutions aim to strengthen KWT product innovation, streamline BUMDesa management, and optimize digital marketing strategies for both business units. It is hoped that this capacity building will encourage more competitive and sustainable local economic growth in Kesiut Village.